2015
DOI: 10.1007/s00018-015-1929-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 in breast cancer: the CK2β regulatory subunit takes center stage in epithelial plasticity

Abstract: Structurally, protein kinase CK2 consists of two catalytic subunits (α and α') and two regulatory subunits (β), which play a critical role in targeting specific CK2 substrates. Compelling evidence shows the complexity of the CK2 cellular signaling network and supports the view that this enzyme is a key component of regulatory protein kinase networks that are involved in several aspects of cancer. CK2 both activates and suppresses the expression of a number of essential oncogenes and tumor suppressors, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 262 publications
1
37
0
Order By: Relevance
“…GSK3β S9 phosphorylation and deactivation is known to regulate the expression of Snail1 protein induced by TGF-β1 in HK-2 cells [49]. Moreover, GSK3β phosphorylation and destabilization of Snail1 requires the priming phosphorylation of Snail1 by CK2, a process reported to be dependent on CK2β [32,61]. However, we have now observed that the LY294002 induced decrease in GSK3β S9 phosphorylation was accompanied by a decrease in Snail1 levels both in control and in CK2β downregulated HK-2 cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…GSK3β S9 phosphorylation and deactivation is known to regulate the expression of Snail1 protein induced by TGF-β1 in HK-2 cells [49]. Moreover, GSK3β phosphorylation and destabilization of Snail1 requires the priming phosphorylation of Snail1 by CK2, a process reported to be dependent on CK2β [32,61]. However, we have now observed that the LY294002 induced decrease in GSK3β S9 phosphorylation was accompanied by a decrease in Snail1 levels both in control and in CK2β downregulated HK-2 cells.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, CK2β might influence substrate specificity, since there are protein substrates whose phosphorylation is specifically catalysed by either the free catalytic subunits or CK2 holoenzyme [3]. Moreover, CK2β also binds to a wide range of other cellular proteins and acts as a regulatory binding partner of certain protein kinases [9][10][11], suggesting that it can exert cellular functions other than its incorporation into CK2 holoenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…CSNK2 is generally considered to be a constitutively active enzyme (i.e., its catalytic subunits do not require activating phosphorylation, association with its regulatory subunit, or the presence of second messengers to be catalytically active), which is expressed at higher levels in many forms of human cancer (1,3,7,8). CSNK2 has also been shown to be essential for viability and to enhance cancer cell survival associated with inhibition of apoptosis.…”
Section: Convergence Of Csnk2 With Caspase Pathwaysmentioning
confidence: 99%
“…CKII contributes to the pathology of many human cancers (21)(22)(23). Multiple complexes containing CKII have been identified, including the transcription elongation factor FACT (16,24).…”
Section: Transcription Elongation By Rna Polymerase II (Rnapii)mentioning
confidence: 99%